The Design of The TU Service Project Monitoring System in PT. GMF Aeroasia Tbk - Erika Ramadhani; Handika Irawan (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2019)
To unit is one of the units in the GMF in the Information & Communication Technology division, one unit is the TOB has a Self Development Application (SDA) task. At present many requests for procurement of goods are submitted to the TU service. This is certainly very influential on TU services that become less optimal and irregular. So a system design was made to monitor the TU Service project. The research method is carried out by analyzing business requirements and business cases. After analyzing the two documents, then make a blueprint containing the system description starting from the explanation of each module or feature and appearance of the system. Then make the interactive prototype as a system simulation. After going through a number of these steps, a monitoring system for the Dinas TU project was developed which could be utilized by the TU Service in project management.